Pengaruh Pengawasan dan Lingkungan Kerja Fisik Terhadap Disiplin Kerja Pegawai Pada Dinas Pendidikan, Kepemudaan, dan Olahraga (DIKPORA) Kota Bima - Erwin hidayah; Firmansyah kusumayadi; Ovriyadin (CV Edujavare Publishing, 2026)
Work discipline is one of the important factors that determine the effectiveness of employee performance in government agencies. Low work discipline can have an impact on the declining quality of public services, so efforts are needed to identify the factors that influence it. This study aims to analyze the influence of supervision and the physical work environment on employee work discipline at the Bima City Education, Youth, and Sports Office (DIKPORA). The study used a quantitative approach with an associative research type. The study population was 86 employees, while the sample was 45 employees with the status of State Civil Apparatus selected using a purposive sampling technique. Data collection was carried out through questionnaires, observations, and literature studies, then analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results showed that supervision had a positive and significant effect on work discipline (t = 2.650; p = 0.011), as did the physical work environment (t = 2.641; p = 0.012). Simultaneously, both variables also significantly influenced work discipline (F = 39.319; p < 0.001) with a coefficient of determination of 65.7%. This finding indicates that improving the quality of supervision and providing a conducive physical work environment can improve employee work discipline at the DIKPORA of Bima City.